FACTORS INFLUENCING ENGLISH ACHIEVEMENT OF HIGH-ABILITY STUDENTS OF CLASS 2A IN THE INFORMATION TECHNOLOGY SYSTEM STUDY PROGRAM AT MUHAMMADIYAH UNIVERSITY OF KOTABUMI ACADEMIC YEAR 2025/2026 - Nur Ramadhani Putri Azka; Dewi Sri Kuning; Yusi Qonita Luthfiya; Ibrohim Hasan; Salma Aulia; Nayla Ayesa; Rasya Sukardi (Universitas Muhammadiyah Kotabumi, 2023)
This study examines the factors influencing the English achievement of high-ability students in class 2A of the Information Technology Systems Study Program at Muhammadiyah University of Kotabumi in the academic year 2025/2026. The purpose of this study was to determine the factors contributing to students' English achievement during their learning process. The subjects were 16 high-ability students who achieved a score above 80 or a final grade of A in relevant courses. This study used a qualitative method with semi-structured interviews as the data collection technique. Data were analyzed through the stages of data collection, data reduction, data display, and conclusion drawing. The results showed that students' English achievement was influenced by six main factors: motivation, prior educational experience, teacher-student relationship, socioeconomic factors, classroom environment, and parental support. These six factors interact with each other in shaping readiness, comfort, and external support that facilitate students' learning success. Overall, students' English achievement is the result of a combination of internal and external factors that complement each other and contribute significantly to the development of students' English achievement.